2012
DOI: 10.1097/spv.0b013e318255b096
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Body Length Among Different Racial Groups in the First Stage of Labor

Abstract: Objective Anatomic differences among racial groups may contribute to observed differences in the occurrence of severe perineal lacerations at the time of vaginal delivery. The purpose of this study was to identify differences in perineal body length between racial groups. Methods Perineal body length was measured in primigravid women aged 18 to 45 years who were admitted in labor. Women were classified into 1 of 6 racial groups: White, Filipino, Japanese, Chinese, Native Hawaiian, or Micronesian. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
18
1
Order By: Relevance
“…Table 1 shows the studies involving PL measurements antenatally, and in the first and/or second stage of labour. The average PL is 39 mm (range 37-41 mm) in the late antenatal period or first stage of labour [26][27][28][29][30][31] and PL has increased by 50-60 % at crowning to 60 mm [31][32][33]. Patients with PL ≤25 mm (measured during the first stage) had a significantly greater risk of OASI (40 % vs. 5.6 %, p= 0.004) [26].…”
Section: Anatomical and Tissue Factors Perineal Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the studies involving PL measurements antenatally, and in the first and/or second stage of labour. The average PL is 39 mm (range 37-41 mm) in the late antenatal period or first stage of labour [26][27][28][29][30][31] and PL has increased by 50-60 % at crowning to 60 mm [31][32][33]. Patients with PL ≤25 mm (measured during the first stage) had a significantly greater risk of OASI (40 % vs. 5.6 %, p= 0.004) [26].…”
Section: Anatomical and Tissue Factors Perineal Lengthmentioning
confidence: 99%
“…Although they found women of Chinese and Filipina descent to have significantly more perineal tears, they found no such differences between vaginal and cervical lacerations. Tsai et al [29] and Lai et al [31] found no difference in PL between women of different ethnic backgrounds. There may be other factors such as fetal weight and head circumference that contribute to a higher rate of severe perineal lacerations between women of certain ethnicities living in their native countries compared to those who become westernised.…”
Section: Impact Of Race/ethnicity On Oasimentioning
confidence: 99%
“…Our average perineal body length was 3.2 cm. This was less than the average perineal body reported in other western studies as 3.7 cm by Lane et al, 3 3.9 cm by Deering et al, 5 and 4 cm by Tsai et al 3,5,7 This difference may be due to racial differences between the studied populations. All the examined patients in our study where African black women; in contrast, in the studies by Lance et al 3 and Tsai et al, 5 only 15% and 18% of the women were black women, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…We also measured perineal body length specifically in the first stage of labor. It is unclear how the perineum changes in length during labor 8 . Clinical observation points to potential dynamic changes in perineal body length in different stages of labor 8 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed on the perineal tears risk factors, and the results of these studies are widely known by healthcare workers, such as nullipara, prolonged second stage, vaginal delivery with instruments, medial episiotomy, persistent posterior occiput position, and macrosomia [ 3 5 ]. However, many health workers neglect patient's perineal structure.…”
Section: Introductionmentioning
confidence: 99%